2023
DOI: 10.21037/tlcr-22-594
|View full text |Cite
|
Sign up to set email alerts
|

BRCA mutations detected by tumour next-generation sequencing in non-small cell lung cancer: impact on response to therapy and disease course

Abstract: Background Data regarding the prevalence and clinical relevance of BRCA mutations in non-small cell lung cancer (NSCLC) is limited. Our objective was to evaluate the impact of pathogenic BRCA variants detected by tumour next-generation sequencing (NGS) on disease course and response to therapy. Methods We performed a retrospective analysis of all consecutive NSCLC patients with available NGS reports in a single insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The fact that, in our cohort, p-BRCA patients exhibited increased sensitivity to PBC and PARPi supports the assumption that, in at least some cases of NSCLC, mutations in BRCA play an oncogenic role and predict response to these treatments. These results also concur with the recent publication by Tschernichovsky et al, which showed prolonged PFS in first-line therapy for seven patients with NSCLC harboring BRCA mutations compared to an institutional cohort [23]. Two BRCA carriers in our cohort had additional somatic BRCA mutations; further HRD testing of tumor tissue samples, especially in cases in which sensitivity to PBC and PARPi was demonstrated, might shed light on the role of BRCA mutations in NSCLC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that, in our cohort, p-BRCA patients exhibited increased sensitivity to PBC and PARPi supports the assumption that, in at least some cases of NSCLC, mutations in BRCA play an oncogenic role and predict response to these treatments. These results also concur with the recent publication by Tschernichovsky et al, which showed prolonged PFS in first-line therapy for seven patients with NSCLC harboring BRCA mutations compared to an institutional cohort [23]. Two BRCA carriers in our cohort had additional somatic BRCA mutations; further HRD testing of tumor tissue samples, especially in cases in which sensitivity to PBC and PARPi was demonstrated, might shed light on the role of BRCA mutations in NSCLC.…”
Section: Discussionsupporting
confidence: 93%
“…This is likely due to the overrepresentation of the Ashkenazi-Jewish population at our center, where the estimated carrier frequency is 2.5% [22]. Indeed, 53.8% of patients in our study were carriers of classical Ashkenazi-Jewish PVs and the prevalence of p-BRCA in NSCLC patients in our study is similar to a recently published cohort of 445 patients with NSCLC treated in a different center in Israel [23]. The fact that only 1% of BRCA carriers at HMC developed NSCLC, together with the relatively older age of diagnosis (median 67 years old), corresponds with previous findings suggesting that BRCA carriers are not at increased risk for developing NSCLC [3,12,13].…”
Section: Discussionsupporting
confidence: 86%